Trends in research and prevention policies for work-related musculoskeletal disorders at the European Agency for Safety and Health at Work (EU-OSHA) - Nakata, Minori (Sangyō eiseigaku zasshi, 2002)
The European Agency for Safety and Health at Work (EU-OSHA) has been working on matters related to occupational health problems in 15 European Union (EU) member states. EU-OSHA established 10 topic centers on work and health research in 1998. One of the topic centers is assigned for research and information on work-related musculoskeletal disorders. The present report is written because such activities of EU-OSHA are scarcely known in Japan. Work-related musculoskeletal disorders have become a very serious problem in EU member states, i.e., 30% of workers complain of backache, and 17% complain of muscular pains in their arms and legs. The affected workers not only suffer at work but also in their home life. The economic costs of all work-related ill health range from 2.6 to 3.8% of the gross national product, and work-related musculoskeletal disorders constitute 40-50% of this. Therefore EU member states consider that prevention of work-related musculoskeletal disorders in itself is an extremely good economic policy. EU-OSHA published "Work-related neck and upper limb musculoskeletal disorders" in 1999, and "Research on work-related low back disorders" in 2000. These publications suggest various preventive methods which can be introduced in practice at work. One of the most remarkable things in EU-OSHA's activities for work-related musculoskeletal disorders is that EU-OSHA has been trying hard to introduce the results of its research into real policies for EU member states by several means, i.e., held a seminar participated in by policy makers, representatives of trade unions, and researchers from EU member states, and sent seminar resolutions to politicians who are responsible for employment and social affairs. Finally the resolution has been adopted in a new social affairs policy by the EU parliament and will be put into force during 2002. Work-related musculoskeletal disorders will remain one of the most serious occupational problems in EU member states, and EU-OSHA will continue to pay close attention to it.